2018
DOI: 10.1055/s-0038-1676345
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Soluble Thrombomodulin in Sepsis-Induced Coagulopathy: An Updated Systematic Review and Meta-Analysis

Abstract: Background Clinical effectiveness of recombinant human soluble thrombomodulin (rhTM) in sepsis or sepsis-induced coagulopathy remains a matter of dispute. Recently, the Sepsis Coagulopathy Asahi Recombinant LE Thrombomodulin (SCARLET) trial, the latest multinational multi-centre phase III randomized controlled trial, was completed. Objective This article assesses the benefits and harms of rhTM therapy in sepsis-induced coagulopathy by updating our previous systematic review. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
(34 reference statements)
0
42
0
2
Order By: Relevance
“…However, a similar efficacy of rhsTM treatment for sepsis-associated coagulopathy was not confirmed in a recent RCT that was conducted by international multi-institutions [53]. In addition, the latest systematic review and metaanalysis did not reveal the advantage of rhsTM treatment for sepsis-induced DIC [54]. Conversely, only a small number of studies reported the effect of rhsTM treatment on DIC complicated with ARDS.…”
Section: Discussionmentioning
confidence: 93%
“…However, a similar efficacy of rhsTM treatment for sepsis-associated coagulopathy was not confirmed in a recent RCT that was conducted by international multi-institutions [53]. In addition, the latest systematic review and metaanalysis did not reveal the advantage of rhsTM treatment for sepsis-induced DIC [54]. Conversely, only a small number of studies reported the effect of rhsTM treatment on DIC complicated with ARDS.…”
Section: Discussionmentioning
confidence: 93%
“…There is a great number of clinical and preclinical reports of successful thrombomodulin treatment in inflammatory conditions (Ito et al 2016). Recombinant thrombomodulin is efficaciously used in Japan to treat patients with disseminated intravascular coagulation in sepsis (Yamakawa et al 2019).…”
Section: Thrombomodulinmentioning
confidence: 99%
“…Another reason is concomitant uses of heparin that counter a benefit of rTM. Although a recent meta-analysis including SCARLET trial found trend toward improved survival, this effect was not statistically significant [11]. Therefore, further rTM trials for septic DIC patients are desirable.…”
Section: Consistency Of Evidencementioning
confidence: 89%